Re-analysis of the current status of clinical trial registration in China - Li, Shuwen; Li, Jianhao; Zeng, Wenjing; Li, Zhicheng; Zhang, Jietong; Wang, Siying; Xu, Nenggui; Li, Zeli (Frontiers in Medicine, 2025)
Objective To reanalyze and summarize the current status and deficiencies of clinical trial registration in China, based on an analysis of the situation of clinical trial registration in the Chinese Clinical Trial Registry (ChiCTR). Methods A search was conducted in China National Knowledge Infrastructure (CNKI), Chinese BioMedical Literature Database (CBM), Wangfang Data, VIP Database for Chinese Technical Periodicals (VIP), Web of Science (WoS), PubMed up to December 31, 2023, for literature on the analysis of clinical trial registration based on ChiCTR. NoteExpress software was used for screening, EXCEL for data organization and analysis, the Word Cloud website for constructing word frequency maps, and Origin software for visualization. Results Among the 94 articles included, common analysis items included the number of registered projects, types of research, registration time, types of registration institutions, and regional distribution. Most of the included literature was funded. The publishing institutions involved 20 provinces/municipalities across the country, with hospitals being the majority of the publishing units. Most literature was submitted shortly after search completion and published shortly after submission, with more than half of the articles published in high-quality journals. The total average citation count of the literature was 3.34. The sources of clinical trial registration platforms analyzed in the literature were divided into three categories: single platform, dual platform, and multiple platforms. Conclusion ChiCTR plays a key role in enhancing transparency in clinical research, promoting standardization and normalization of research, strengthening domestic and international scientific research cooperation, and advancing medical innovation and public health improvement. However, there are still issues with the quality of registration, focus areas, and the evaluation of registration quality.